Question

Prove that :$$\dfrac{cos \, A}{1 \, - \, sin \, A} \, + \, \dfrac{sin \, A}{1 \, - \, cos \, A} \, + \, 1 \, = \, \dfrac{sin \, A \, cos \, A}{(1 \, - \, sin \, A)(1 \, - \, cos \, A)}$$

Solution

we have$$\Rightarrow \, \, \, LHS \, = \, \dfrac { cos \, A}{1 \, - \, sin A} \, + \, \dfrac { sin \, A}{1 \, - \, cos A} \, + \,1$$$$\Rightarrow \, \, \, LHS \, = \dfrac { cos A (1 \, - \, cos A ) \, + \, sin A (1 \, - \, cos A ) \, + \, (1 \, - \, sin A )(1 \, + \, cos A) }{ sin A (1 \, - \, cos A ) \, + \, (1 \, - \, sin A )(1 \, + \, cos A) }$$$$\Rightarrow \, \, \, LHS \, = \dfrac { cos A \, - \, cos^2 A \, + \, sin A \, - \, sin ^2 A \, + \, 1 \, - \, sin A \, - \, cos A \, + \, sin A cos A}{ sin A (1 \, - \, cos A ) \, + \, (1 \, - \, sin A )(1 \, + \, cos A) }$$$$\Rightarrow \, \, \, LHS \, = \, \dfrac {(cos A \, + \, sin A) \, -\, (cos^2 A \, - \, sin ^2A ) + \, 1 \, - \, ( cos A \, + , sin A) \, + \, sin A cos A }{ sin A (1 \, - \, cos A ) \, + \, (1 \, - \, sin A )(1 \, + \, cos A) }$$$$\Rightarrow \, \, \, LHS \, = \, \dfrac{ (cos A \, + \, sin \, A) - \, 1 \, + \,1 \, - \, ( cos A \, + \, sin A) \, + \, sin A \, + \, cos A}{ sin A (1 \, - \, cos A ) \, + \, (1 \, - \, sin A )(1 \, + \, cos A) }$$$$\Rightarrow \, \, \, LHS \, = \dfrac {sin A \, cos A}{ sin A (1 \, - \, cos A ) \, + \, (1 \, - \, sin A )(1 \, + \, cos A) }$$ $$= RHS$$ Mathematics

Suggest Corrections

0

Similar questions
View More

People also searched for
View More